Evolution of the SpoIISABC Toxin-Antitoxin-Antitoxin System in Bacilli - Marek Gabriško; Imrich Barák (Toxins, 2016)
Programmed cell death in bacteria is generally associated with two-component toxin-antitoxin systems. The SpoIISABC system, originally identified in Bacillus subtilis, consists of three components: a SpoIISA toxin and the SpoIISB and SpoIISC antitoxins. SpoIISA is a membrane-bound protein, while SpoIISB and SpoIISC are small cytosolic antitoxins, which are able to bind SpoIISA and neutralize its toxicity. In the presented bioinformatics analysis, a taxonomic distribution of the genes of the SpoIISABC system is investigated; their conserved regions and residues are identified; and their phylogenetic relationships are inferred. The SpoIISABC system is part of the core genome in members of the Bacillus genus of the Firmicutes phylum. Its presence in some non-bacillus species is likely the result of horizontal gene transfer. The SpoIISB and SpoIISC antitoxins originated by gene duplications, which occurred independently in the B. subtilis and B. cereus lineages. In the B. cereus lineage, the SpoIIS module is present in two different architectures.